Malaysia's efforts in pursuit of new public diplomacy: methods, challenges and strategies / Imran Ariff Mohammad Amin - Mohammad Amin, Imran Ariff (2019)
Public diplomacy has established itself as one of the most important core in the field of diplomacy of the transformations in the global politics since the 20th century onwards. The turning point of the transformations in global politics came at the end of the Cold War in the 1990s, with the non-existence of a two polar system (Soviet Bloc vs US Bloc i.e. Blue vs Red) the world politics came to its own evolution thanks to globalization. New public diplomacy came about thanks also to globalization. With the practise of soft power employing nation branding, digital diplomacy and cultural diplomacy takes precedes compared to use of force and superior military strength to gather alliances and public support, states started to give importance to the support of their public diplomacy efforts, which also adds more legitimacy to their foreign policies. Malaysia being a moderate nation sees itself competing to be a middle power and it is only logical and feasible in order to succeed while competing with the superpowers that Malaysia have to employ methods of Soft Power by gaining the ability to affect others to obtain the outcomes Malaysia wants through attraction and persuasion rather than coercion or payment is more crucial now for the country’s survival in multilateral politics and a matter of public opinions. Wisma Putra and the government have to put new efforts into the nation’s public diplomacy policies. Once a country that is looked up to by other ASEAN peers and an Asian Tiger, Malaysia is now on a downhill battle amongst our regional neighbours who are faring better in this arena. Malaysia efforts in pursuit of new public diplomacy is more needed now than ever for the new the political direction that our country is heading and also to better credibility and image once again. The paper will look into the feasibility and importance of doing so based on adopting theories and concepts that are widely practiced now on public diplomacy as advocating a smart public diplomacy policy required, and an understanding of the roles of credibility, self-criticism, nation branding, hetropolarity and public perceptions in generating soft power that will work for us while understanding the needs for a local recipe based on geo-political and cultural needs not to mention identifying the obstacles and challenges that needs to be overcomes in order to achieve the required success.